Characterization of Plasmids of Escherichia coli Isolated from Mastitis - Avinash Ganpatrao Karpe (Department of Microbiology, College of Veterinary and Animal Sciences, 1993)
Escherichia coli were isolated in 15.33 per cent cases of mastitis. Of the 46 E. coli isolated 43 were resistant to one to nine antibiotics and three were sensitives to all the 13 antibiotics tested. The organisms were resistant to rifampicin (78.26%) followed by oxytetracycline (50%), tetracycline (37.78%), nalidixic acid (19.56%), co – trimoxasole (8.69%) and gentamicin (6.52%). All the organisms were susceptible to kamamycin and norfloxacin. Among the multiple drug resistance oxytetracycline – rifampicin (OR) resistance was noticed in 76.2% cases. Twenty – six different patterns of antibiotic resistance were noticed among 43 E. coli isolates giving a reliability of 60.46 per cent in differentiating the isolates. Hence antibiogram could only be used as an adjunct to plasmid profiling in epidemiological studies. The resistograms revealed cent per cent resistance to lead, followed by antimony (32.6%), copper (30.43%), silver (19.56%) and cetrimide (2.17%). All the isolates were sensitive to cadmium and mercury. Among the 46 E. coli isolates, 9 different resistogram patterns were obtained giving reliability of 19.56 per cent in differentiating the strains. A correlation between the antibiotics and heavy metal resistance such as lead, antimony and copper, was observed in descending order. Of the forty – six E. coli isolates three (6.52%) were haemolytic on sheep blood agar. Two of the three haemolytic strains were also enterotoxigenic. Thirteen of the 46 (28.26%) E. coli isolates were enterotoxigenic, when tested by rabbit ligated ileal loop assay. Two of the thirteen (15.38%) enterotoxigenic isolates were also haemolytic. Fourteen of the 24 (58.33%) drug resistant E. coli transferred drug resistance against one or more antibiotics to the recipient organism. In none of the cases the furazolidone resistance was transferred. All the three haemolytic E. coli isolates transferred the haemolytic character by conjugation indicating the plasmid borne nature of hemolysin production. None of the enteroxin producing E. coli could transfer the character to recipient by conjugation. Of the 40 wild E. coli screened for plasmid profiles two were devoid of any plasmid. The number of plasmids varied from one to five with molecular size ranging from 1.47 to 128.8 kb. Among the thirty – eight plasmid bearing E. coli isolates, altogether 35 different plasmid profile patterns were obtained as six E. coli isolates showed three different plasmid profiles. The isolates with similar plasmid profiles revealed similar antibiogram, resistogram and Ent character. The haemolytic strains contained large as well as small plasmids. Only large plasmids, along with haemolytic character and drug resistance were transferred to the recipient. It indicated that the plasmids carrying genes for hemolysin production also harboured antibiotic resistance genes. In case of enterotoxigenic E. coli (ETEC) the Ent character was not transferred by conjugation, which could be due to the location of the character on small plasmids which are nonconjugative. Two of the three ETEC strains which were haemolytic, transferred the HIy character, but not the Ent character to the recipient E. coli. Ethidium bromide was found to be the best curing agent among the chemicals used. The degree of curing increased with the time of exposure. Ethidium bromide cured R – factors, Hly, Ent and F’lac characters. Furazolidone resistance was neither transferred by conjugation nor cured. But nalidixic acid resistance was eliminated by EB. Elevated temperature (450 C) cured antibiotic resistance Hly, Ent, F’lac characters. The rate of curing increased from fifth day onwards. Large plasmids were eliminated in all the cases. The study of, transfer of plasmids by conjugation, their elimination by curing, and plasmid profiles of wild, transconjugant and cured strains of E. coli revealed correlation between plasmid and virulence characters. There was a definite correlation between Hly character and antibiotic resistance as they were co – transferred on conjugation and the traqnsconjugants harboured only one large plasmid exhibiting these two characters. The photographic technique developed with ordinary single lens reflex camera, resulted in colour photographs with better resolution. This technique could serve as a substitute to polaroid camera system. The results obtained from the present study led to the following conclusions. * Indiscriminate use of antibiotics should be dispensed with and antibiogram should be carried out prior to treatment. The drugs of choice were kanamycin, norfloxacin, gentamicin, co – trimoxazole, furazolidone and nalidixic acid. * The antibiogram and resistogram could serve as an adjunct to plasmid profile analysis in epidemiological studies. * The role of plasmids in the production of hemolysin, enterotoxin and the antibiotic resistance was established. * Ethidium bromide was found to be the best chemical curing agent, whereas elevated temperature (450 C) showed the best curing effect among physical and chemical methods of curing. * Only larger plasmids could be transferred by conjugation. Plasmid profile analysis could be used in differentiating and identifying E. coli strains and thus serves as a better epidemiological tool. * There was a correlation between hemolysin production and antibiotic resistance since both the characters were co – transferred and co – eliminated. * Photographic technique of plasmid DNA with ordinary singly lens reflex camera was found to serve as a substitute to polaroid camera system.